2007
DOI: 10.1245/s10434-007-9593-3
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity in Breast Cancer Patients with Sentinel Node Metastases Undergoing Delayed Axillary Lymph Node Dissection (ALND) Compared with Immediate ALND

Abstract: A two-stage axillary node dissection procedure in patients with SLN metastases has similar arm morbidity to one-stage ALND. The second surgery is associated with increased axillary operative time and total hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 7 publications
4
40
0
2
Order By: Relevance
“…As outlined above, the plateau in upper limb volume 2 years after surgery suggests that estimates of lymphedema rates at 2 years may be an accurate estimate of the long-term rates of lymphedema after RAC. This is consistent with the results of a long-term cohort study in which 77% of patients with lymphedema developed it within 3 years after RAC [12]. Patients can also be advised that the risk of a significant increase in upper limb volume developing after axillary clearance is about 1 in 6.…”
Section: Discussionsupporting
confidence: 88%
“…As outlined above, the plateau in upper limb volume 2 years after surgery suggests that estimates of lymphedema rates at 2 years may be an accurate estimate of the long-term rates of lymphedema after RAC. This is consistent with the results of a long-term cohort study in which 77% of patients with lymphedema developed it within 3 years after RAC [12]. Patients can also be advised that the risk of a significant increase in upper limb volume developing after axillary clearance is about 1 in 6.…”
Section: Discussionsupporting
confidence: 88%
“…This is in keeping with work by Giuliano et al who demonstrated an overall complication rate of 3% after SNB compared with 35% post-ALND [23]. Although it is possible that a SNB followed by an axillary dissection might have greater morbidity than an axillary dissection alone, the ALMANAC trial showed no significant difference in post-operative morbidity between SNB (with delayed ALND) and the group who underwent ALND alone [24]. In addition to documented improvements in morbidity, improved psychological well being has been observed in patients who undergo SNB relative to ALND [9].…”
Section: Discussionsupporting
confidence: 87%
“…Evaluation of arm and breast morbidity included the rates of lymphedema, pain, neuropathy, and reduced range of motion in the ipsilateral arm. At 6-12 mo after surgery, all these outcomes were less frequent in SLNB patients than in ALND patients (34,(40)(41)(42)(43)(44)(45). Table 1 summarizes the framework and results of the most important randomized controlled trials comparing SLNB and SLNB 1 ALND SLNB in the management of breast cancer.…”
Section: Cancer Indications Breast Cancermentioning
confidence: 99%